Dampak Aktivitas Pemulung Anak Di Tempat Pembuangan Akhir, Kelurahan Manulai II - J. Moukoni, Aleksander; A. Lao, Hendrik; Wira Syahputra, Andrian (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This research describes the activities of child scavengers at the Manulai II Village Final Disposal Site (TPA). The aim of this research is to obtain data and an overview of children's scavenger activities at the landfill along with the impacts arising from this activity as well as solutions to deal with problems arising from these activities. The subjects of this research were child scavengers who were actively carrying out their work every day as scavengers at Manulai II TPA, aged 7-14 years and who were at high risk of educational problems and working conditions that were not conducive to their survival. The research method used in research on the activities of child scavengers at TPA Manulai II is descriptive qualitative with a case study approach. The aim of using this method is to describe in detail the activities of child scavengers at the TPA which is the target of the research. In addition, the use of this method is not to focus on differences that will later be developed into generalizations but to detail the specifics of the unique context. The main informants taken in the case study of children's scavenger activities at TPA Manulai II were four people, and of the four informants, two were still at school and the other two were no longer in school. The research results showed that the informants came from poor families and they worked to help their families and to meet their own needs even though they were still children. The informant experiences problems related to physical and psychological conditions and requires services that must be met immediately, especially the need for education, health, attention from the environment, the need for love from family and society. Problem solving plans created by the author through the "Child Scavenger Eradication and Development Program Who Work in TPA Through Family Care". The aim of this program is to attract children out of the dangerous work environment at the landfill into a family environment, because the family is the right place for children's growth and development and at the same time can reduce the number of child scavengers working at the landfill. This program provides services in the form of social guidance for children and family, providing education costs, health services and providing business capital assistance. The program targets for child scavengers who work at TPA are children, families and the community.